Assembling Shreds of History: dance and memory of the last Argentine civic-military dictatorship - Cadús, María Eugenia (2020)
The article analyzes the play Retazos pequeños de nuestra historia más reciente (2010) choreographed by Daniel Payero for the Compañía Nacional de Danza Contemporánea, and its approach to the memory of the last Argentine civic-military dictatorship (1976-1983). Throughout this analysis, the article offers some thoughts on the embodied memory or the embodiment of the dictatorship’s memory as a repertoire or performance. How and what kind of memory do the dancing bodies have and evoke? Here, performance as embodied memory is presented as a fragmentary montage that alters the common place of official memory, allowing an intimate and affective dimension to arise.